Public Perspectives and Suggestions on Improving the Components of Malaysia Dam Safety Management Guidelines (MyDAMS) - Sidek L.M.; Muhammad Z.; Basri H.; Khambali M.H.M.; Azhan A.F.; Ali Z.; Omar J. (Springer Science and Business Media Deutschland GmbH, 2024)
In September 2017, the Department of Irrigation and Drainage Malaysia (DID) inaugurated the first national guidelines for the safety management of dams in Malaysiatitled Malaysia Dam Safety Management Guidelines (MyDAMS). The goal of MyDAMS is to safeguard people, their possessions, and the environment from dam disasters. This guideline applies to dam owners, operators, engineers, consultants, regulatory bodies, and other related organizations that are responsible for dam safety. After 5years, it is advisable to investigate the effectiveness of MyDAMS by measuring the level of understanding and practice of MyDAMS among the public. Thus, a survey was conducted among dam owners, operators, dam engineers, consultants, researchers, and related organizations in the dam sector. Results showed that MyDAMS is effective among the public as they are used daily, especially in the Dam Safety Management System. The public is also satisfied with MyDAMS as it covers all aspects of dam safety management from the planning stage to decommissioning. This study contributes to dam safety in Malaysia in two ways: 1. Discovery of public perspectives on the first dam safety guidelines in MalaysiaMyDAMS. 2. Delivery of public opinion and recommendations to improve MyDAMS to ensure the validity of the guidelines. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.